Secondary Metabolites from Carica papaya, and its Biological Activities: A Comprehensive Review - Amr Adel; Mohamed S. Elnaggar; Eman Al-Sayed; Mohamed A. Rabeh (Ain Shams University, 2021)
Carica papaya L. is the most well-known species of family Caricaceae. The edible tropical plant was widely used in traditional folk medicine worldwide and known for possessing high nutritional and medicinal values in all its parts such as fruit, leaf, seed, and latex. This review provides a comprehensive literature survey of the biological activity and the isolated phytochemical compounds reported in Carica papaya. The phytochemical research reported the isolation of several classes of phytochemicals including flavonoids, alkaloids, phenolic acids, fatty acids, sterols, triterpenes, saponins, and isothiocyanates and other miscellaneous compounds. The review also focused on the wide range of biological activities reported from crude extracts and fractions of different parts used from the Carica papaya plant that can contribute in finding alternative therapeutic approaches to combat various health problems and improve the health of the people suffering from those problems. The various biological activities feature the need for further studies to explore the bioactive compounds responsible for the biological activities and their mechanism of action.